VOICES UNDER PRESSURE: AN EXPLORATION OF SPEAKING ANXIETY AMONG PRESERVICE EFL TEACHERS DURING TEACHING PRACTICUM - Deni Asrida; Siska Febriyanti; Eka Surya Bayu (English Study Program University of Pasir Pengaraian, 2025)
Speaking anxiety remains a persistent challenge for preservice EFL teachers, yet its manifestation within teaching practicum has received limited contextual investigation. This qualitative study explores the factors shaping English-speaking anxiety among ten preservice teachers at UIN Mahmud Yunus Batusangkar. Data were generated through semi-structured interviews, reflective journals, and field notes and analysed using Braun and Clarke’s thematic analysis. The findings reveal that speaking anxiety emerges from the interaction of internal and external factors rather than isolated linguistic deficiencies. Internal sources include linguistic insecurity, fear of negative evaluation, low teaching self-confidence, and inadequate pedagogical preparation, while external pressures stem from evaluative audiences, sociocultural norms, and unpredictable classroom conditions during practicum. By conceptualizing speaking anxiety as an ecological and contextually situated phenomenon, this study extends the predominantly cognitive and psychological literature on foreign language anxiety and demonstrates how sociocultural and practicum-specific conditions jointly shape preservice teachers’ experiences. The findings contribute to teacher education by highlighting the importance of integrating linguistic support, psychologically safe feedback practices, and scaffolded practicum experiences to foster professional confidence and communicative resilience.